ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL PERSAMAAN KUADRAT BERDASARKAN TAKSONOMI SOLOPADA KELAS X SMA NEGERI 1 PLUS DI KABUPATEN NABIRE – PAPUA - Ronald Manibuy; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2014)
Abstract: The objectives of this research were to describe the position of errors, kind of errors and factor that caused students’ errors in answering quadratic equation questions based on SOLO taxonomy on the X grade students of SMA with high, moderate and low mathematics ability. This research was a descriptive qualitative. This research was carried out on the X grade students of SMA Negeri 1 Plus Nabire – Papua. The written data were taken from the result of mathematics ability test and first problem solving test (M1: linear/quadratic pattern) and the second problem (M2: functional concept), the oral forms data were taken from the result of interview which were conducted to the subject of the research to get valid data 1 and valid data 2. Afterwards, the valid data were analyzed to find out the constant level of consistency achievement of SOLO level, in order to meet reliable data from the chosen research subjects 2 students with high mathematics ability, 3 students with moderate mathematics ability and 2 students with low mathematics ability. The valid and reliable data were used to analyze students’ errors based on SOLO taxonomy. The result of the research showed that: (a) the students with high mathematics ability were reached unistructural–relational level, (b) the students with moderate mathematics ability were reached unistructural–multistructural level, (c) the students with low mathematics ability were almost reached unistructural level. Errors made by the research subjects: (1) all of students conducted the same errors in answering the mathematics model of the quadratic equation questions, they did not provide the answer correctly and they did not understand the concept of the questions properly, (2) kinds of errors including: (a) misconception, not comprehending about quadratic concept, this error existed in all mathematics ability levels. Whereas errors on the concept of variable, which is used to form the mathematics quadratic equation, was conducted by moderate and low level subject; (b) error on the principle, the application of the mathematics rules and formulas incorrectly in answering the quadratic equation questions, was conducted by high, moderate and low levels; (c) operational error was often conducted by low, moderate and high deals with the operational of algebra, especially on the calculation of negative integer operation, (3) the factors that caused errors for the research subjects of high, moderate and low levels were low comprehension on mathematics’ concept, principle and operation.  Keywords: errors analysis, quadratic equation, SOLO taxonomy